THE CONCEPT CONSTRUCTION OF INDONESIAN LANGUAGE E-MODULE DEVELOPMENT BASED ON TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE IN INCLUSIVE SENIOR HIGH SCHOOLS IN BALI PROVINCE - I Made Suarta; Ida Ayu Agung Ekasiadi; I Komang Sukendra (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
The Indonesian language e-module in inclusive schools plays a crucial role in coordinating students, including those with special needs. Technological Pedagogical Content Knowledge (TPACK) is a framework that emphasizes the importance of integrating technology and pedagogy in educational content development. This study aimed to: (1) develop a TPACK-based e-module for inclusive senior high schools and (2) explore and analyze the concept of an Indonesian language learning e-module based on TPACK in inclusive senior high schools. The research employed both qualitative and quantitative approaches with the following stages: (1) exploring and analyzing the implementation of TPACK in inclusive senior high schools and (2) constructing a draft concept for a TPACK-based Indonesian language e-module. The e-module development followed the IDDEI model. This approach provides new guidance for teachers in implementing technology in learning, ensuring that teaching and learning activities are conducted effectively and efficiently in alignment with 21st-century demands, where teachers are required to be proficient in applying technology. The findings revealed that the developed e-module was valid, practical, and effective, making it suitable for use in Indonesian language learning, particularly in drama materials. The advancement of science and technology can be leveraged to enhance the quality of learning, and teachers need to understand and possess TPACK competencies. Therefore, the use of TPACK-based e-modules in inclusive senior high schools is essential, and the concept of Indonesian language e-module development based on TPACK needs to be implemented.